The disturbances in the power system due to environmental conditions - Nigam, Manoj Kumar; Koshta, Vaibhav (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> In most of our electronics and electrical devices are very sensitive to the real voltage and current values and other parameters. A slight fluctuation in the voltage and in the current may damage the devices. Therefore proper care needs to be taken for the proper functioning of these devices. But at the same time we cannot neglect the effect of environmental conditions on the devices used in the power system. The environmental conditions such as rainfall, heat, wind, humidity, thundering and lightning etc. has a significant influence on various electrical parameters and also even in the transmission lines. Taking the various environmental conditions into the account the efficiency and the reliability to the devices and the power system can improved. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>